(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
By explicitly recognizing an «interest of future generations», the recent reform to the article 9 of Italian Constitution gives rise to a renewed discussion of the main conceptual and institutional predicaments in view of realizing true and proper avenues for intergenerational justice. In this paper, I will sketch the major ethical, as well as political and legal problems regarding this matter, while also depicting – by means of a legal-phenomenological investigation – an apt model of representation and recognition, such that future-oriented claims may find a genuine space for their acknowledgment and expression.